Peguatan Loyalitas Konsumen Ritel Lokal melalui Peningkatan Suasana Toko, Keragaman Produk, Pelayanan, Persepsi Harga, dan Promosi - Sudin Sudin; Rahma Rahma; I Gusti Nyoman Surya Utama (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
Local retailers in Banyuasin face competition from modern retail, requiring strategies to strengthen customer loyalty. This study aims to explore strategies for enhancing customer loyalty through store atmosphere, product variety, service quality, price perception, and sales promotion. This research employed a qualitative approach using SWOT analysis and a four-step framework. Data were collected through observation and interviews with local retail managers in Banyuasin. The results show that a comfortable store atmosphere, diverse product offerings, friendly and fast service, competitive pricing, and creative promotions significantly improve customer loyalty. Furthermore, external opportunities such as modern shopping trends, social media utilization, and government support also enhance loyalty strategies. The findings highlight the importance of integrating internal strategies with external opportunities. These insights provide a foundation for local retailers to develop more sustainable marketing strategies. This study concludes that customer loyalty can be strengthened through an integrated strategy that combines internal and external factors. The findings provide important implications for the development of local retail management.